Effects of (In)Congruency in Fertility Motivation on Fertility Desire and Intention Among Couples Living with HIV: A Dyadic Approach - Guo Y; Liu J; Du Y; Chongsuvivatwong V (International Journal of General Medicine, 2023)
Yingwu Guo,1,2,* Jun Liu,1,* Yingrong Du,1,* Virasakdi Chongsuvivatwong2,* 1Department of Infectious Diseases, Third People’s Hospital of Kunming City, Kunming, People’s Republic of China; 2Department of Epidemiology, Faculty of Medicine, Prince of Songkla University, Hat Yai, Songkhla, Thailand*These authors contributed equally to this workCorrespondence: Virasakdi Chongsuvivatwong, Department of Epidemiology, Faculty of Medicine, Prince of Songkla University, 15 Kanjanavanich Road, Hat Yai, Songkhla, 90110, Thailand, Tel +66897350098, Email cvirasak@medicine.psu.ac.thBackground: Fertility decision-making plays a negligible role in completing fertility goals among couples living with HIV (CLWH). Being commonly matched concerning fertility motivation seems essential for fertility desire/intention. Few studies report on intra-couple congruences or incongruences in fertility motivation on desire/intention. This study aims to assess the effects of (in)congruency in fertility motivation on fertility desire and intention among couples living with HIV.Methods: This study uses the actor-partner interdependence model (APIM) to assess the independent direct and indirect effect of fertility motivation on intention, and dyadic response surface analysis with congruency/incongruent effect (DRSA) of fertility motivation on intention using fertility desire as mediator variable among CLWH. CLWH were selected from a clinic in Kunming, China, between October and December 2020. Cross-sectional research included 314 CLWH.Results: APIM revealed that the wife’s fertility motivation had an indirect influence on fertility intention of couples mediated by her fertility desire (R2 = 0.42). There was a significant effect on fertility intention by interaction of (in)congruency in fertility motivation among couples. DRSA shows that linear congruency in fertility motivation of both husband and wife increased fertility desire and intention of couples. However, if there was an incongruent in fertility motivation among husband and wife, husband’s domination in fertility motivation was common and negatively affect the wife’s fertility desire to have a child. Overall, couples who were matched on fertility motivation reported a significant greater relationship with fertility intention than couples who were mismatched.Conclusion: Counseling could help both the husband and wife achieve a greater positive fertility intention by addressing comparable fertility goals.Keywords: (in)congruency, dyadic data analysis, Traits-Desires-Intentions-Behavior model, couples living with HIV